New and little-known miridae from French Guyana and neighbouring areas (Hemiptera: Heteroptera) - Chérot, Frédéric (2016)
New data on thirty-four species of plant bugs (Insecta: Hemiptera: Heteroptera: Miridae) of French Guyana are provided. This number includes descriptions of two new species, Papaveronia matocqi sp. nov. and Urucuiana linnavuorii sp. nov., and thirty-two species cited for the first time from this country: Amapacylapus amapariensis Carvalho and Fontes, 1968; Calondas fasciatus Distant, 1884; Ceratocapsus brunneus Henry, 1983; Creontiades rubrinervis (Stål, 1862); Cylapocoris fulvusWolski, 2013; Cylapocoris simplexWolski, 2013; Cyrtocapsus xinguanus Carvalho, 1984; Engytatus varians (Distant, 1884); Henicocnemis amazonicusCarvalho and Costa, 1993; Horciasinus humeralis (Berg, 1892); Horciasoides minensis (Carvalho, 1976); Horciasoides notatus (Distant, 1884); Horciasoides plagosus (Distant, 1884); Krainacoris rondoniensisCarvalho and Costa, 1993; Macrolophus cuiabanus Carvalho, 1945; Macrolophus praeclarus Distant, 1884; Minytus cuiabanusCarvalho, 1975; Monalocorisca conspurcata Reuter, 1913; Monalonion atratum Distant, 1883; Neoleucon panamensis Carvalho, 1988; Neostenotus bifasciatus (Carvalho and Fontes, 1972); Notholopus nigerCarvalho and Costa, 1992; Notholopus sulcaticornis (Stål, 1860); Poeas goianaCarvalho, 1989; Prepops circummaculatus (Stål, 1854); Prepops tupianus Carvalho and Fontes, 1970; Proba vittiscutis (Stål, 1860); Pycnoderes amapaensis Carvalho, 1984; Pycnoderes atratus (Distant, 1884); Spartacus albatus Distant, 1884; Taedia dispersaCarvalho and Costa, 1993 and Trigonotylus tenuis (Reuter, 1893). Neostenotus bifasciatus is also cited for the first time from Suriname.